1994
DOI: 10.1113/jphysiol.1994.sp020459
|View full text |Cite
|
Sign up to set email alerts
|

The processing of human ballistic movements explored by stimulation over the cortex.

Abstract: 1. When seated human subjects abducted one arm rapidly in response to a tone there was successively a burst of electromyographic (EMG) activity in the deltoid and latissimus dorsi muscles followed by another burst in the deltoid muscle. This triphasic pattern is typical of a ballistic 'focal movement'. There were also bursts of EMG activity in the contralateral latissimus dorsi, pectoralis major and abdominal muscles, which were assumed to be 'associated postural adjustments'. The same bilateral pattern of mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…In this case, SRT may be slightly shortened, while the processing in the motor cortex is actually disrupted by TMS. Therefore this study will have an important implication in experiments in which TMS is used in combination with the simple reaction paradigm (FitzGibbon et al 1993;Priori et al 1993;Palmer et al 1994). Lack of proper knowledge about IF can lead to a total misunderstanding of brain function studied by TMS, especially in terms of changes in SRT.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, SRT may be slightly shortened, while the processing in the motor cortex is actually disrupted by TMS. Therefore this study will have an important implication in experiments in which TMS is used in combination with the simple reaction paradigm (FitzGibbon et al 1993;Priori et al 1993;Palmer et al 1994). Lack of proper knowledge about IF can lead to a total misunderstanding of brain function studied by TMS, especially in terms of changes in SRT.…”
Section: Discussionmentioning
confidence: 99%
“…Although ballistic movements about a single joint are commonly characterized by a triphasic (agonist-antagonist-agonist) electromyographic (EMG) pattern of activity (Angel 1975;Marsden et al 1983;Virji-Babul and Cooke 1995;Palmer et al 1994), some authors observed another activation strategy that involves a high level of agonist/antagonist coactivation instead of the three successive phases (Mustard and Lee 1987;Cooke and Brown 1990;Carpentier et al 1999). The latter strategy is also often reported in ballistic actions when there is no requirement to stop the movement (Mustard and Lee 1987;Carpentier et al 1999), in multijoint movements (Marsden et al 1983;Osternig et al 1986;Lee et al 1999) and during isometric contractions (Van Cutsem and Duchateau 2005).…”
Section: Introductionmentioning
confidence: 93%
“…In both modes the execution of ballistic focal movements and the accompanying postural adjustments is considered to be preprogrammed (Cordo & Nashner, 1982). It has been suggested that postural adjustments are generated in close connection with focal ballistic movements and an intact motor cortex is indispensable for their execution (Palmer, Cafarelli & Ashby, 1994; Palmer, Downes & Ashby, 1996).…”
mentioning
confidence: 99%